KLASSIKALÍQ TEŃSIZLIKLERDI DÁLILLEWDE TRANS TEŃSIZLIGIN QOLLANÍW USÍLLARÍ - Kalekeeva, T.T.; Shamenova, J. (ILIM hám JÁMIYET, 2022)
The article discusses methods for proving classical inequalities using Cauchy’s inequalities with respect to the mean, inequalities between geometric and harmonic means, inequalities between quadratic and arithmetic means, Cauchy-Bunyakovsky-Schwarz inequalities, Shebichev’s inequalities.